Las ampliaciones de la Unión Europea hacia Europa del Este: impacto político, económico y social - Rodríguez, Pedro Manuel (Nómadas. Critical Journal of Social and Juridical Science, 2017)
This article addresses the impact that EU membership has had on the countries of Eastern Europe. During 2004, 2007 and 2013, a considerable number of countries of the former Eastern European socialist block were incorporated into the UE, ending in this way with the legacy of socialism. On the other hand, this article studies growth and economic development among the Eastern European countries that have joined the EU and the countries of the "new Eastern Europe", which do not belong to the EU. Finally, this article is based on the Complex Security Theory. In the concluding remarks, the author stresses that the integration of Eastern European countries into the EU responded to political and economic interests of “both Europes”. Nevertheless, the most important among those interests was security.